Phytopathogenic fungi associated with avocado seed (Persea american Mill.) - Leon Ttacca, Betsabe (2016)
A series of fungi diseases severe is disseminated by avocado seeds and they can decrease the production in approximately 14% and a reduction of quality in 10%. The present investigation consisted in to isolate and identify pathogens fungal present in the avocado seeds mexican race used for patron. The fotopatogenos fungi were isolated in culture medium Sucrose Agar Potato from the embryo and cotyledon of 200 seeds of avocado and to identify with taxonomic keys also was carried out Pathogenicity test on avocado plants with the most frequent phytopathogenic fungi. The pathogens fungal isolated and identiﬁed from embryo and cotyledon of seeds were Lasiodiplodia sp. with 0.5% and 1.00%, and Fusarium sp with 1.50% and 2.50% of frecuency respectively. The pathogenicity test allowed conﬁrming that Lasiodiplodia theobromae and Fusarium verticillioides affect to seedlings of avocado, being the source of primary inoculum and means of dissemination infected seeds by these pathogens.